PLANNING OF “SEKOLAH PENGGERAK“ IN EDUCATION QUALITY ESCALATION EFFORTS - Safitri, Anisa Mega Nur; Triwiyanto, Teguh; Sobri, Ahmad Yusuf; Sultoni, Sultoni (International Education Trend Issues, 2023)
Escalating the quality of education can be done with various means and efforts. One of them is the escalation of the quality of education by initiating the “Sekolah Penggerak” . Escalation requires changes and careful planning to achieve educational goals. Therefore, the planning process built on school resources can be one of the steps in achieving educational goals. This research aims to find out the planning of the “Sekolah Penggerak” to escalate the quality of education. The method used is descriptive qualitative, with data collection using interviews, observation, and documentation techniques. The results of this study are 1) conducting a planning process through PBD, IRB, RKT, and SWOT analysis; 2) conducting school development strategies through mindset alignment, asset management, HR development, partnerships, TPMPS optimization, budget, and time; 3) establishing driving school guidelines, and 4) setting driving school goals and expectations